Submission and subjection in Leviathan good subjects in the Hobbesian commonwealth - Byron, Michael 1964- (Palgrave pivot, 2015)
"In Leviathan, Thomas Hobbes famously characterizes the state of nature as a predicament in which life is "solitary, poor, nasty, brutish, and short." The only means of escape from that dire condition is to found the commonwealth, with its notorious sovereign. Hobbes invests the sovereign with virtually absolute power over the poor subjects of the commonwealth, and that vast and unlimited sovereign has drawn the reader's eye for 350 years. Yet Hobbes has a great deal to say about subjects in a commonwealth as well, and he articulates a normative conception of a good subject. This book develops a novel interpretation of the role of submission in Leviathan, and it introduces the concept of subjection to explain the expectations Hobbes has for good subjects"--Back cover